Add new comment

Permalink In reply to by Anonymous (not verified)

for any equation p(x)=0 (where p(x) is an expression or function of x) has roots a0, a1,....then at x=a0, a1,... p(x) becomes 0. in your example, p(x)=1 - x^2/4. At x=2 or -2, i.e., p(2)=p(-2) = 0.

Filtered HTML

  • Web page addresses and email addresses turn into links automatically.
  • Allowed HTML tags: <a href hreflang> <em> <strong> <cite> <code> <ul type> <ol start type> <li> <dl> <dt> <dd>
  • Lines and paragraphs break automatically.